2021
DOI: 10.3389/fbioe.2021.670124
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administrable Therapeutic Nanoparticles for the Treatment of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common and lethal human malignancies worldwide; however, the therapeutic outcomes in the clinic still are unsatisfactory due to the lack of effective and safe therapeutic regimens. Orally administrable and CRC-targetable drug delivery is an attractive approach for CRC therapy as it improves the efficacy by local drug delivery and reduces systemic toxicity. Currently, chemotherapy remains the mainstay modality for CRC therapy; however, most of chemo drugs have low wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 192 publications
0
20
0
Order By: Relevance
“…However, each brings its own advantages and disadvantages, and an effective formulation for colon carcinomas has not been developed yet. From this point of view, novel drug delivery systems and nanoparticular drug delivery systems are considered and evaluated as trends and promising approaches in the treatment of colon carcinomas as well as of many other diseases [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, each brings its own advantages and disadvantages, and an effective formulation for colon carcinomas has not been developed yet. From this point of view, novel drug delivery systems and nanoparticular drug delivery systems are considered and evaluated as trends and promising approaches in the treatment of colon carcinomas as well as of many other diseases [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the LNPs employed for the treatment of colorectal cancer are via oral route. It was observed that the LNPs are absorbed from the intestinal lumen into the circulation of colorectal region through endocytosis or via carrier-mediated transport [ 159 ]. Similarly, for treating hepatocellular carcinoma (liver cancer), LNPs are presently under pre-clinical and clinical trials.…”
Section: Clinical Statusmentioning
confidence: 99%
“…The formulation was well tolerated; however, there is a need for further clinical studies on the combination of the formulation with fluoropyrimidines [ 109 ]. Ying et al reported the oxaliplatin which was encapsulated into PEG-coated cationic liposomes [ 110 ] and long-circulating liposomes (PEG-liposomal oxaliplatin). The effects of PEG-liposomal oxaliplatin on a tumour formed by a human CRC cell line (SW480) in female BALB/c nude mice were studied.…”
Section: Nanoparticles Loaded With Platinum Drugs For Colorectal Canc...mentioning
confidence: 99%